Playing TETris with DNA modifications. (13th May 2014) - Delatte, Benjamin; Deplus, Rachel; Fuks, François
Abstract Methylation of the fifth carbon of cytosine was the first epigenetic modification to be discovered in DNA. Recently, three new DNA modifications have come to light: hydroxymethylcytosine, formylcytosine, and carboxylcytosine, all generated by oxidation of methylcytosine by Ten Eleven Translocation (TET) enzymes. These modifications can initiate full DNA demethylation, but they are also likely to participate, like methylcytosine, in epigenetic signalling per se. A scenario is emerging in which coordinated regulation at multiple levels governs the participation of TETs in a wide range of physiological functions, sometimes via a mechanism unrelated to their enzymatic activity. Although still under construction, a sophisticated picture is rapidly forming where, according to the function to be performed, TETs ensure epigenetic marking to create specific landscapes, and whose improper build‐up can lead to diseases such as cancer and neurodegenerative disorders.